Below the belt [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2017)
When he does a favor for an old friend which involves damaging information that could cause an explosive quagmire for those in the highest offices, Stone Barrington may hold the key not just to one man's fate, but to the fate of the nation.